"I have no control over how much time I play" the metacognitions about online gaming scale: Evidence from a cross-cultural validation among Israeli adolescents. (June 2023) - Efrati, Yaniv; Spada, Marcantonio M.
Highlights: The factorial structure of the Hebrew MOGS comprised the expected two factors at T1 and T2 (a six-month follow-up) Metacognitions significantly mediated the effect of attachment styles on IGD and the motives for online gaming. Hebrew MOGS appears psychometrically appropriate for prevention and treatment of IGD. Abstract: In the current study we evaluated the psychometric properties of the Metacognitions about Online Gaming Scale (MOGS), including its factor structure, reliability, and predictive validity among Israeli adolescents in a six-month prospective study. We also examined the usefulness of the MOGS as a mediator of the effect of attachment patterns on Internet Gaming Disorder (IGD), the preference for online social interactions, and the motives for online gaming. The study population included 1, 056 Israeli adolescents (610 males and 446 females, M = 15.77, standard deviation (SD) = 1.43) with an age range of 13–18 years. The participants completed the translated Hebrew version of the MOGS and measures on attachment style, IGD, preference for online social interactions, emotion regulation, and motives for online gaming. The analyses indicated that the factorial structure of the Hebrew MOGS comprised the expected two factors at T1 and T2 (a six-month follow-up). We also found that positive and negative metacognitions significantly mediated the effect of attachment styles on IGD, the preference for online social interactions, and the motives for online gaming. The findings provide evidence that the Hebrew MOGS among Israeli adolescents appears psychometrically appropriate for use by researchers and practitioners dealing with the prevention and treatment of IGD.